2019
DOI: 10.17116/oftalma201913503155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of diabetic retinopathy in pregnancy

Abstract: РЕЗЮМЕВведение. Беременность является фактором риска прогрессирования диабетической ретинопатии (ДР). Несмотря на распространенное мнение о регрессе ДР после родов, возможно агрессивное течение процесса, приводящее при несвоевременном лечении к потере зрительных функций.Цель -представить клинические случаи с различным течением ДР у беременных с сахарным диабетом 1-го типа (СД1). Материал и методы. Обследовано 5 беременных, страдающих СД1 более 8 лет. У всех пациенток уровень гликемии был выше нормы (гликирован… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several potential risk factors are introduced to initiate or progress DR among patients with type 2 diabetes mellitus, including the duration of diabetes, hypertension, advanced diabetic nephropathy, severe carotid artery occlusive disease and pregnancy 10,11 . Furthermore, Scanlon et al showed that race plays an important role in the progression of DR among various populations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Several potential risk factors are introduced to initiate or progress DR among patients with type 2 diabetes mellitus, including the duration of diabetes, hypertension, advanced diabetic nephropathy, severe carotid artery occlusive disease and pregnancy 10,11 . Furthermore, Scanlon et al showed that race plays an important role in the progression of DR among various populations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…DR-related biomarkers are found in blood, retina, vitreous, and aqueous humor and have also recently been found in tears [ 15 ]. The development of DR occurs progressively and pregnancy is a risk factor for it [ 16 ]. DR is graded according to the clinical features associated with it.…”
Section: Reviewmentioning
confidence: 99%